Cardiovascular Risk Factors and Atherogenic Indices in an Iranian Population: Birjand East of Iran - Kazemi, Toba (Clin Med Insights Cardiol, 2018)
Introduction: The alteration in serum lipid profile; increase in total cholesterol (TC), triacylglycerol (TAG), and low-density lipoprotein cholesterol (LDL-C); and reduction in high-density lipoprotein cholesterol (HDL-C) are key factors in cardiovascular disease progression. The high prevalence and severity of cardiovascular diseases require new screening tools for better evaluation. Atherogenic index (AI) (LDL-C/HDL-C) and coronary risk index (CRI) (TC/HDL-C) can be strong markers for predicting the risk of atherosclerosis and coronary heart disease and disclose the presence of LDL or TAG in the serum of related patients. To implement this strategy, the AIs and CRIs in our population were assessed. In this study, a total of 5207 subjects were recruited and AIs and CRIs were calculated for all of them. According to our data, age, body mass index, sex, as well as CRI and AI had affirmative correlation with TC, LDL-C, TAG, systolic blood pressure, and diastolic blood pressure. By increasing these factors, AIs and CRIs were augmented. Moreover, in situations where all atherogenic parameters are normal, these parameters may be the alternative screening tool.